Regulation system study for innovative communication services - Soonho Hong (International Telecommunications Society (ITS), 2011)
The change in the telecommunication market can be explained with the change within the traditional telecommunication services and the introduction of new innovative services. In accordance with the changing telecommunication environment from Fixed/Circuit/Voice to Wireless/Packet/Data, each country is trying to improve its regulatory system and to build the infrastructure appropriate for the change. This study suggests the principals required for regulatory systems to vitalize innovative telecommunication services. It is make a road and let it be used freely. By comparing the regulatory environment of the U.S., EU and Korea about their policies for Fixed/Wireless networks, ex post regulations and net neutrality, the implications necessary to lead the future telecommunications market are suggested. In conclusion, the U.S. has its strength in Fixed networks, EU has it in Wireless networks and Korea needs to make a blue print of future networks which has not yet been experienced by any country of the world and, at the same time, needs to build a flexible regulatory system.
Keywords: 330; Regulation; Telecommunication; Innovative Service; Fixed/Wireless Network; Ex post; Net Neutrality; U.S.; EU; Korea